PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA GURU DI LINGKUNGAN UPTD PENDIDIKAN KECAMATAN GATAK SUKOHARJO - Budiastuti, Mahendrati -; Rahadhini, MD - (Universitas Slamet Riyadi, 2010)
ABSTRACT The objective of this research is to analyze about the significance influence of leadership, work motivation, and experiences to the teacher’s performance of education environment in UPTD at Gatak Sukoharjo. The populations are teachers in education environment in UPTD at Gatak Sukoharjo in 2010 amount of 498 respondents. Sampling has random for 50 teachers. Collecting data uses observation, interview and questionaire. Instrument test uses validity and reliability tests. Analysis techniques used classical assumption test, multiple regression analysis, t test, F test and coefficient determination (R2). The results shown that (1) validity and reliability shown valid and reliable, (2) heteroskedasticity, autocorrelation, multicolinearity and normality tests were passed, (3) regression equation Y = 2,340 + 0,212 X1 + 0,348 X2 + 0,578 X3, (4) leadership has p value < 0,05; work motivation has p value < 0,05; and teacher’s experience has p value < 0,05; so all three variables are significantly influences to the teacher’s performance, (5) teacher’s experience has most dominant influence to teacher’s performance because it has highest coefficient regression as 0,578; F test has p value < 0,05, (6) adjusted R2 = 0,479, means that ratio contribution leadership, work motivation and work experience to the teacher’s performance as 47,9% and the remains are influenced by other factors. Keywords: leadership, work motivation, work experience, and teacher’s performance